Local and global existence of mild solutions for a class of nonlinear fractional reaction-diffusion equations with delay - Zhu, B.; Liu, Lishan; Wu, Yong Hong (Elsevier, 2016)
In this paper, we investigate the local and global existence of mild solutions to a class of nonlinear fractional reaction-diffusion equations with delay via the theory of ß-resolvent family and fixed point theorems.